2009
DOI: 10.4155/bio.09.11
|View full text |Cite
|
Sign up to set email alerts
|

The 2nd Calibration and Validation Group Workshop on Recent Issues in Good Laboratory Practice Bioanalysis

Abstract: This event was organized by the Calibration and Validation Group (a scientific nonprofit organization based in Toronto, Canada) as a 1.5-day workshop for contract research organizations and pharmaceutical companies involved in providing bioanalytical data for bioavailability, bioequivalence, pharmacokinetic and comparability studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…Discussions continued in 2008, where it was confirmed that ISR was being successfully implemented within the industry, although there were still clarifications needed regarding the amount of samples necessary and the final criteria to be used [2]. The following year, consensus stipulated that the number of samples to be re-assayed for the ISR evaluation should be between 5% and 10%, based on the attendees' experiences in LCMS [3].…”
Section: Incurred Sample Reanalysismentioning
confidence: 99%
See 4 more Smart Citations
“…Discussions continued in 2008, where it was confirmed that ISR was being successfully implemented within the industry, although there were still clarifications needed regarding the amount of samples necessary and the final criteria to be used [2]. The following year, consensus stipulated that the number of samples to be re-assayed for the ISR evaluation should be between 5% and 10%, based on the attendees' experiences in LCMS [3].…”
Section: Incurred Sample Reanalysismentioning
confidence: 99%
“…In 2008, consensus was reached that the evaluation of hemolysis effects was required [2]. Following continued discussions in 2009, 2010 and 2011, it was recommended to at least investigate the impact of hemolysis during method development since agency trends demonstrate that this evaluation is requested [3,4,5].…”
Section: Hemolysis Testing (Lcms)mentioning
confidence: 99%
See 3 more Smart Citations